Sound absorption of electrospun polyvinylidene fluoride/graphene membranes. (September 2016) - Wu, Chang Mou; Chou, Min Hui
Graphical abstract: Highlights: ES membranes absorb sound in the middle-frequency region by friction and vibration. The ES PVDFs converted sound to electric potential in low-frequency region. Graphene enhanced PVDFs' piezoelectricity and further shifted to lower frequency. Abstract: In this study, a novel sound-absorbing material was developed using electrospun piezoelectric polyvinylidene fluoride (PVDF) membranes. The effects of graphene (Gp) and electrospinning on the crystal structure and piezoelectric properties of PVDF/Gp nanofibrous membranes were examined. The results showed that electrospinning effectively induced the beta phase and increased the piezoelectricity. Adding graphene further improved the piezoelectric properties through interfacial polarization. Electrospun nanofibrous membranes exhibited an increase in surface area, and, consequently, their contact with sound waves was increased, which enhanced the sound-energy absorption in the middle-frequency region through the friction and vibration of the internal nanofibers. The piezoelectric electrospun PVDF samples were crucial for converting sound energy into electric potential and absorbing sound waves in the low-frequency region, and the sound absorption performance of the electrospun PVDF/Gp membranes with the highest piezoelectricity was shifted further to a lower frequency region. Thus, the electrospun PVDF/acoustic nonwoven presented herein is potentially a practical and efficient sound absorber because of its favorable absorption performance, particularly in low-frequency regions.